Pengaruh Media Flash Card Terhadap Hasil Belajar Siswa Kelas V Mata Pelajaran IPS di SDN Banjarsari 2 - Rika Nurhasanah; Ribut Prastiwi Sriwijayanti; Ryzca Siti Qomariyah (CV. ITTC INDONESIA, 2023)
Learning media is anything that can be used to convey messages from the teacher to students so that they can stimulate the mind, feelings, interests, and students' attention so that the learning process can take place effectively. The problems that occurred at SDN Banjarsari 2 in class V showed that many students tended to feel bored, students looked lacking active in the learning process, and the material presented is difficult for students to understand. It was from here that the researcher was interested in conducting research entitled The effect of flashcard media on the learning outcomes of fifth grade students in social studies at SDN Banjarsari 2. Based on the background of the problems that have been occurs, then it is formulated